2005
DOI: 10.1271/bbb.69.922
|View full text |Cite
|
Sign up to set email alerts
|

Thermostability of Refolded Ovalbumin andS-Ovalbumin

Abstract: Ovalbumin, a member of the serpin superfamily, is transformed into a thermostabilized form, S-ovalbumin, during storage of shell eggs or by an alkaline treatment of the isolated protein (DeltaT(m)=8 degrees C). As structural characteristics of S-ovalbumin, three serine residues (Ser164, Ser236 and Ser320) take the D-amino acid residue configuration, while the conformational change from non-thermostabilized native ovalbumin is very small. To assess the role of the structural characteristics on protein thermosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…The turbidity measurements showed that these peptides did not affect the aggregation kinetics of OVA at 80°C. 32 IAIMSA 37 of hB induced the formation of long straight fibrils of OVA without significantly changing the aggregation kinetics, an effect on OVA fibril formation similar to that caused by reduction of the disulfide bond between Cys 73 and Cys 120 . Therefore, the effect of 32 IAIMSA 37 on OVA aggregation could be explained by the interaction of 32 IAIMSA 37 and hB to promote a conformational change.…”
Section: Mvlvmentioning
confidence: 86%
See 4 more Smart Citations
“…The turbidity measurements showed that these peptides did not affect the aggregation kinetics of OVA at 80°C. 32 IAIMSA 37 of hB induced the formation of long straight fibrils of OVA without significantly changing the aggregation kinetics, an effect on OVA fibril formation similar to that caused by reduction of the disulfide bond between Cys 73 and Cys 120 . Therefore, the effect of 32 IAIMSA 37 on OVA aggregation could be explained by the interaction of 32 IAIMSA 37 and hB to promote a conformational change.…”
Section: Mvlvmentioning
confidence: 86%
“…32 IAIMSA 37 of hB induced the formation of long straight fibrils of OVA without significantly changing the aggregation kinetics, an effect on OVA fibril formation similar to that caused by reduction of the disulfide bond between Cys 73 and Cys 120 . Therefore, the effect of 32 IAIMSA 37 on OVA aggregation could be explained by the interaction of 32 IAIMSA 37 and hB to promote a conformational change. A previous study on the loop insertion of serpin showed that serpin polymerization may be blocked by peptide fragments of the reactive center loop (54).…”
Section: Mvlvmentioning
confidence: 86%
See 3 more Smart Citations